Pengaruh Pengumuman UU No 21 Tahun 2011 Tentang Pembentukan Otoritas Jasa Keuangan Terhadap Return Saham di Bursa Efek Indonesia Sektor Keuangan - Arie Agus S; Symasurijal Tan; Enggar Diah Puspa Arum (Jurnal Akuntansi & Keuangan Unja, 2018)
This study aims to determine the reaction of the announcement of Law No. 21 Year 2011 is the formation of the Otoritas Jasa Keuangan of the stock returns that occurred in Indonesia Stock Exchange in the financial sector. Sampling is by purposive sampling method with required data criteria fulfilled. Data analyst technique used is to use Event Study to see whether or not abnormal return that occurred during the observation period of the study. The results of this study indicate that there is an abnormal return during the observation period which occurs significantly at t-14, t-9 before the announcement of Law No. 21 Year 2011 and t +4, t + 6 after the Law No. 21 Year 2011 is announced by the government. Keryword: Announcement of Law no. 21 Year 2011, Study Event, Return Share and Abnormal Return Shares.